Bagworm (Pteroma Pendula Joannis) and Its Control by Entomopathogenic Fungi, (Metarhizium Anisopliae Metchnikoff and Paecilomyces Fumosoroseus Wize) - Cheong, Yew Loong (2009)
Pteroma pendula (Joannis) was the dominant bagworm species infesting oil palm Plantation, Hutan Melintang, Lower Perak. This species had six instar stages when reared in the laboratory condition. The ratio of molting for late instar did not follow Dyar’s rule. Dimorphism was observed in pupa and imago stages. Female emerged as apterous and vermiform-like, and male emerged as moth. Pteroma pendula had a lifespan of 50.4 ± 1.8 days in laboratory condition. Length of the cases were significantly correlated with head capsules for both male (R2= 0.97) and female (R2= 0.92) and might be useful in estimation of the instar stage in field. Rainfall frequencies were found not significantly correlated with the outbreak of the bagworms in the study site, thus the outbreak did not influenced by rainfall. Field observation recorded the natural populations of bagworms were being controlled by predators, parasitoids and pathogenic fungi. Through systematic sampling of bagworms from the study site, the natural enemies had caused mortality to 4.85% of the bagworm population, and this was ineffective in keeping the bagworm populations below the economic threshold level (five to ten bagworms per frond).